The image and social status of female musicians in Taiwan - Pan, Li-Ming (2014)
In Taiwan, female musicians who play Western classical music have often been considered a group with a fixed image regarding their appearance. The stereotype is common amongst Taiwanese people, including female musicians. It has become an important criterion for assessing whether an individual can be considered legitimate as a female musician. Although the visual factor plays a critical role for Taiwanese female musicians, it has never been seriously investigated. This thesis aims to establish why and how the stereotype is formed, what elements constitute the favoured image, what messages are sent by the principal components, what is its mechanism and how does it affect the life and career of female musicians in Taiwan. First, the thesis traces the development and current condition both of women’s status and of Western classical music in Taiwan to clarify the position of female musicians in Taiwanese society. Due to its association with the hegemonic cultural and imperial powers/domination of the West, Western classical music is considered the embodiment of progress and civilisation in Taiwan. Female musicians are also deemed a group of high class and with an appealing image. This particular status has usually made them popular and advantageous in the marital market. This is partly revealed from the analyses of newspaper reports. The statistics in the present study show that, when female musicians are discussed in newspapers, most topics centre on their marriage and appearance. This demonstrates how most people think of female musicians and which aspects of female musicians are considered important in Taiwanese society. After reviewing the background of the status of female musicians, the thesis analyses what elements constitute the stereotype by scrutinizing the concert poster. The concert poster can be viewed as the most influential medium for displaying female musicians’ images, because of its prevalent circulation, its focus upon directly displaying the appearance of female musicians, and the fact that it is produced by the musicians themselves. The images of female musicians on their posters demonstrate high similarity. The thesis examines the critical elements of the posters by comparing them with ancient and modern women’s images. Through investigating these elements and the culture in which they are rooted, the meanings and connotations involved in the poster image will be clearly demonstrated. The findings show that most images of female musicians are designed from the angle of the male gaze. The interview data further illustrate that the posters are not only designed to satisfy the male gaze, but also relate to real men’s looking pleasure and interests in many cases. This thesis undertakes interviews with 17 female musicians. These in-depth conversations with the participants reveal why most female musicians are brought up to be musicians. It is often a decision made from an early age by their parents due to the gendered stereotype and partly to enhance their marital prospects. Nonetheless, whether or not they conform to the image significantly influences their partner searching and career development. Most participants are so accustomed to the image that it is often hard to detect its presence and operation. Through the examples of the social event and the experiences of the participants, the thesis intends to denaturalise the stereotype. It also explores the possibility of changing the image through concert posters.